Vestibular Preservation After Cochlear Implantation Using the Round Window Approach - Tsukada, Keita; Usami, Shin-ichi (Frontiers in Neurology, 2021)
Background: The development of less traumatic surgical techniques, such as the round window approach (RWA), as well as the use of flexible electrodes and post-operative steroid administration have enabled the preservation of residual hearing after cochlear implantation (CI) surgery. However, consideration must still be given to the complications that can accompany CI. One such potential complication is the impairment of vestibular function with resulting vertigo symptoms. The aim of our current study was to examine the changes in vestibular functions after implantation in patients who received CI using less traumatic surgery, particularly the RWA technique. Methods: Sixty-six patients who received CI in our center were examined by caloric testing, cervical vestibular evoked myogenic potential (cVEMP) and ocular VEMP (oVEMP) before or after implantation, or both, to obtain data on semicircular canal, saccular and utricular function, respectively. Less traumatic CI surgery techniques were performed by using the RWA and insertion of flexible electrodes such as MED-EL FLEX soft, FLEX 28, and FLEX 24 (Innsbruck, Austria). Results: Caloric response and the asymmetry ratio of cVEMP and oVEMP were examined before and after implantation using less traumatic surgical techniques. Compared with before implantation, 93.9%, 82.4% and 92.5% of the patients showed preserved vestibular function after implantation based on caloric testing, cVEMP and oVEMP results, respectively. We also examined the results for vestibular functions by a comparison of the 66 patients undergoing the RWA and 17 patients who underwent cochleostomy. We measured responses using caloric testing, cVEMP and oVEMP in patients after CI. There were no differences in the frequencies of abnormal caloric and oVEMP results in the implanted ears between the RWA and cochleostomy. On the other hand, the frequency of abnormal cVEMP responses in the implanted ears in the patients who received implantation by cochleostomy was significantly higher than that in the patients undergoing the RWA. Conclusion: Patients receiving CI using less traumatic surgical techniques have good vestibular function. The RWA is preferable to other approaches in terms of a decreased risk of damage to vestibular function.